Efektivitas ILM (Iklan Layanan Masyarakat) Terhadap Tingkat Pengetahuan, Sikap, Dan Motivasi Tentang Bahaya Napza Pada Siswa SMPN 12 Balikpapan - Nurhasanah Fitriana; Ismail AB; Riza Hayati Ifroh (Jurnal Kesehatan Masyarakat Mulawarman (JKMM), 2020)
Background & Objective: NDPS (Narcotics Drugs and Psychotropic Substances) are substances of drugs when it abused will cause physical, psychological, and dependency disorders. Adolescents aged (12-17 years) are at high risk for starting to use NDPS. To overcome this, it requires health education that more interesting and easy to understand by student as a form of prevention of NDPS abuse. For example, is through radio broadcast PSA (Public Service Announcement) at school. This research aim to find out the effectiveness of radio broadcast PSA to increase knowledge, attitudes and motivations regarding the dangers of NDPS abuse and its prevention for the student of SMPN 12 Balikpapan. Method: The type of this research is quantitative research method by using pre experiment with one group pre test and post test design. The study was conducted at SMPN 12 Balikpapan with 40 students as a samples. The data were processed and analyzed using Paired T-test and Wilcoxon test. Results: The results of data analysis showed that there is a differences level of knowledge, attitudes, and motivation before and after intervention of PSA broadcasts (p-value < 0,05). Conclusion: PSA is effective to increase student's knowledge,attitudes, and motivation to preventing the use of NDPS.